The Last-Minute Struggle : A Systematic Review of Students' Procrastination on Final Projects - Putri Rahmadhani, Syaira; Dwi Cahya Izzati, Indah; Thahir, Andi; Yoki Pradikta, Hervin (Psikoborneo: Jurnal Ilmiah Psikologi, 2026)
Final-year students working on their theses face heavy academic pressure, causing most students to experience stress. This stress leads to academic procrastination and slows down students in completing their final assignments. This study aims to explain the factors, impacts, and strategies that can be used to reduce procrastination through a Systematic Literature Review (SLR) approach. Data were collected from databases based on Scopus, SinceDirect, DOAJ, and Garuda using specific keywords, through the stages of time frame, selection, and classification of articles, resulting in 18 articles selected through PRISMA. The results show that academic procrastination is influenced by psychological factors such as self-regulation and self-efficacy, as well as environmental factors such as family and peer support, and technology. Procrastination will have an impact on delays in completing studies and even the emergence of the desire to drop out. To reduce procrastination, one can practice mindfulness and manage smartphone use. These findings provide a clear picture of academic procrastination that can serve as a guide for students to reduce academic procrastination.Mahasiswa akhir yang sedang mengerjakan skripsi memiliki tekanan akademik yang berat, sehingga sebagian besar mahasiswa mengalami stres. Stres ini berdampak pada prokrastinasi akademik dan memperlambat mahasiswa mengerjakan tugas akhirnya. Penelitian ini bertujuan untuk menjelaskan faktor, dampak, dan strategi yang bisa digunakan untuk menekan prokrastinasi melalui pendekatan Systematic Literature Review (SLR). Data dikumpulkan dari databest berbasis Scopus, SinceDirect, DOAJ, dan Garuda dengan kata kunci tertentu, melalui tahapan kerangka waktu, pemilihan dan klasifikasi artikel yang menghasilkan 18 artikel yang dipilih melalui PRISMA. Hasilnya menunjukan bahwa prokrastinasi akademik dipengaruhi oleh faktor psikologi seperti self regulated dan self efficacy, dan dipengaruhi juga oleh faktor lingkungan seperti dukungan keluarga dan teman sebaya, serta dpengaruhi juga oleh teknologi. Prokrastinasi akan berdampak pada keterlambatan penyelesaian studi bahkan munculnya keinginan untuk dropout. Untuk mengurangi prokrastinasi bisa dengan melatih mindfulness dan mengelola penggunaan smartphone. Temuan ini memberikan gambaran yang jelas mengenai prokrastinasi ak ademi yang bisa menjadi panduan bagi mahasiswa untuk mengurangi prokrastinasi akademik.